Come see the Earth turn : the story of Léon Foucault - Mortensen, Lori, 1955- (Tricycle Press, 2010)
Explores the life and work of nineteenth-century French physicist Leon Foucault, who invented a pendulum that provided proof that the Earth rotated on its axis.